Gestión de cartera vencida en el Comercial Electro Muebles de la Ciudad de Babahoyo - Lara Rojas, Arcelia Dellanira (2018)
The companies that are dedicated to offering products or services to their potential clients, whether they are obliged or not to keep accounts have two ways of making their sales: cash and credit. For most potential customers it is of great importance that when they go to buy a product they sell it on credit, they are necessary for their daily living and sometimes they do not have cash to cancel said good. For companies, granting a loan is very important because it attracts more clients willing to cover needs. It is a risk that is run by not having the necessary customer information or other important factors that make the credit granted to be paid to the agreed date or in the greater case, the debt will never be canceled. The case study was carried out in the Comercial Electro Muebles. It is a one-person natural company required to keep accounts and its activity is the retail sale of household items such as: televisions, sound equipment, washing machines, dryers, furniture for the living room, kitchens, refrigerators, 16 ring bicycles, 20, 24 and 26 among others. The main objective of this research is to know how is the management of the credit portfolio that the Commercial performs at the time of making a sale on credit and will be done through the technique of observation and direct interview, in addition to having knowledge as the owner to raise the portfolio granted to customers. In order to know what are the various factors that this problem entails, the case study was carried out with the topic Management of past due portfolio in the Comercial Electro Muebles of the City of Babahoyo. The development of the case study is a prerequisite for obtaining the Engineering Degree in Accounting and Auditing, as well as establishing the research lines of the two Engineering Degree in Accounting and Auditing from the Faculty of Administration, Finance and Information Technology of the Technical University of Babahoyo, which is directed in the line of research "Financial Management and Social Commitment" belonging to the sub line "Accounting Information Management" .